The differential diagnosis of psoriasis - Kerkhof, Petrus Cornelis Maria van de (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
In general the diagnosis psoriasis can be made on clinical grounds. The differentiation from eczema and other erythematosquamous eruptions is of importance. If a biopsy is indicated, it is important to take it from the margin of the lesion. Characteristic phenomena such as micropustules of Kogoj,microabscesses of Munro and the characteristic topography are usually seen in the material taken from the margin of the lesion and not from the central areas.
Keywords: Dermatitis, allergic contact; Dermatitis, atopic; Dermatitis, seborrheic; Diagnosis; Diagnosis, differential; Eczema; Parapsoriasis; Pathology; Pityriasis rosea; Psoriasis